Comparing the Urine Ketone Strip Test and the Handheld Ketone Meter to Diagnose Ketosis in Early Lactation Dairy Cows - Klibs N. Galvão; Achilles Vieira Neto; Gustavo Peña; Joao Bittar; Lucas Ibarbia (EDIS)
Ketosis is a common metabolic disease in fresh dairy cows. Clinical and subclinical ketosis (SCK) can cause reduced milk yield, decreased milk protein, reduced reproductive capacity, and increased risk of displaced abomasum. Usually, diagnosing ketosis is performed by measuring acetoacetate or BHBA levels in the blood, urine, or milk samples. Measuring BHBA in serum or plasma is considered the gold standard diagnostic test for subclinical ketosis, because this method has stability, but the price for ketone strips is approximately $0.08/strip while the price for the electronic BHBA measuring system is approximately $1.00. UF/IFAS researchers conducted a study to compare the two, using 72 Holstein cows between 14–40 days in milk from three dairy farms in north-central Florida with 450–800 lactating dairy cows. The key finding for this experiment is that no difference exists in BHBA concentration between cows that had a trace or small in the ketone strip reading. This 3-page fact sheet was written by Klibs N. Galvão, Achilles Vieira Neto, Gustavo Peña, Joao Bittar, and Lucas Ibarbia, and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, October 2012.